ANALISIS KEPATUHAN PT BANK RAKYAT INDONESIA (PERSERO) Tbk PADA REVISI PSAK 60 - Longgorung, Lisa Christy; Ilat, Ventje (Universitas Sam Ratulangi, 2017)
Statement of Financial Accounting Standards (SFAS) 60 adjustment in 2014 is a standard that governs the disclosure of financial instruments. This greatly affects the standard of disclosure of details of banking information Indonesia on financial assets in the financial statements, as the industry is highly regulated, allegedly the level of compliance of the Bank Rakyat Indonesia (BRI) to implement the standard was high. Financial assets consist of available-for-sale, held to maturity, loans and receivables, and financial assets at fair value through profit or loss. This study aimed to see if the BRI bank disclose financial assets in accordance with SFAS No. 60 adjustment, 2014. The research method is descriptive qualitative. The results showed BRI bank in the disclosure of their financial assets in accordance with SFAS No. 60 adjustment in 2014 but the management did not express because the default has been completed and the loan terms have been renegotiated before the end of the reporting period. Bank BRI to apply IAS 60 and keep abreast of revisions in accordance with the specified standard. So that transparency in the disclosure of financial statements BRI clearer and can build higher trust of our customers and shareholdersKeywords : bank,disclosure, financial instrument